Efecto del sexo y variación individual sobre respuestas de comportamiento y desempeño de bovinos Simbrah - Grajales-Cedeño, Joseph (2024)
The aim of this study was to evaluate the effect of sex and individual variation on the behavioural responses and performance of Simbrah bovines subjected to a habituation process to human interaction and exposure training. Nineteen animals were used (8 females and 11 males). Reactivity was assessed through points in the restraint cage (1-5), a score for cage exit speed (1-2), and body weight in five assessments over 86 days. Linear mixed models and the effect of individual variations were adopted through a linear regression for each animal, using the b coefficients to classify the animals as habituated, neutral and sensitized. The sex of the animal did not affect the reactivity in the restraint cage, or the cage exit speed (p>0.05); however, reactivity decreased from day 16 (p<0.05) in relation to day 0 in both reactivity scores. There were individual differences in reactivity in the restraint cage and in body weight. On this, 74% of the animals became accustomed to the handling procedure, 21% showed neutral responses in the restraint challenge and 5% were sensitized. In turn, all animals gained weight at different levels, with positive, significant b coefficients (p<0.05) and R2 >0.70. In conclusion, the process of habituation to human interaction and exposure training consistently reduced the reactivity of the animals, without altering their productive performance; however, individual differences must be considered during handling procedures.